Genetic Transmission of ADHD and Nocturnal Enuresis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The transmission of primary nocturnal enuresis (PNE) in relatives of PNE and control probands, with and without ADHD, was examined at the University of California at Los Angeles.